Does the Globalisation Impact on the Science Policy in Russia? - Irina Dezhina (Foresight and STI Governance, 2008)
The paper presents an overview of the four up-to-date science policies in Russia, the example of which can be traced to the effects of globalization. It is referred to the new priorities in support of scientific research, the development of international relations, HR policy, and foreign borrowing instruments in the field of commercialization of research and development (R&D).